Experimental Analysis of Hybrid Wind Diesel Energy System Software Module. (2018) - Mashyal, Suresh; Anil, T.R.
Abstract: The work deals with Hybrid wind diesel power system. The developed software predicts the optimum wind turbine characteristics like cutin speed, cutout speed and rated speed to suit the particular location. The developed module shows variation of power generation by the wind machine with respect to change in wind speed. The operations of different system components like windmill, diesel engine, load, Flow path of power and battery status are simulated. The various charts generated by module helps to predict the performance of hybrid system. The designed software can also be used for monitoring of existing hybrid wind diesel engine system. Visual basic- 6 software is used for writing the program to design wind mill of particular location and MATLAB codes are written to evaluate the amount of power generation by the windmill at a particular wind speed. The designed software results and MATLAB results are carried out followed with experimental data to validate the results. The comparison shows a close agreement between results obtained from developed software, MATLAB outputs and results obtained from experimental setup.